'We dislike to see suffering': the fight for humane slaughter in the United States in the 1950s. Issue 1 (2nd January 2019) - Deutsch, Christopher
ABSTRACT: The history of consumption in the United States has long been marked by its political nature though historians have struggled to explain the politics of consumption and food retailing during the 1950s, when the notion of abundance became synonymous with the United States. This article explores that history by examining the passage of the Humane Methods of Slaughter Act of 1958. Though not a major bill, it enshrined animals' right to die without pain and marked a triumph of animal welfare groups' political activism. By exploring the fight between proponents and opponents of humane slaughter, the nature of consumer politics in the 1950s comes into focus. Consumers fought to force the meat commodity chain to reflect their values as Americans who saw themselves as the most modern and moral nation in the world. Opponents tried to block a mandatory humane slaughter law. Ultimately, proponents succeeded because they framed humane slaughter as an issue of consumer morality. Consumers used the political system to remake a portion of the food economy in order to make food production and retail systems reflect their values.